Application of experience economy tools in the hotel industry - J. A. Pshenichnykh; A. P. Adamyuk (Вестник университета)
Modern trends in the tourism and hospitality industry, influenced by the pandemic and increasing competition, are actualizing the need to find new innovative approaches to managing the development of hotel enterprises to increase the social and emotional value of hotel services for consumers. The ability of the hospitality business to make the desired impression on the consumer will determine its competitive position and success in the market. Insufficient coverage of fundamentally important issues related to the study of the essence of the concept of impression economics, insufficient theoretical consideration of the theoretical and methodological aspects of the concept of impression economics in the management of the development of hospitality enterprises confirm the relevance and purpose of this study. The work examined the essence of the concept, the main ideas, and trends of recent years in the field of the formation of the impression economy; an attempt was made to use the terminology and tools of the impression economy in relation to the hotel product.